Analisis Pemahaman Integral Taktentu Berdasarkan Teori APOS (Action, Process, Object, Scheme) pada Mahasiswa Tadris Matematika (TMT) IAIN Tulungagung - Sholihah, Ummu; Mubarok, Dziki Ari (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2016)
This research aims to describe the understanding ofmathematics Tadris students ofÂ  IAIN TulungagungaboutÂ  indefinite integral understanding of APOS theory. The subjects of research are six students. Each two haveÂ  high, average, and low abilities. The result of the research indicated that the understanding ofmathematics Tadris (TMT) students ofÂ  IAIN Tulungagung about indefinite integral understanding on actionaspect of APOS theory, high students achieve all of understanding indicators, for average students also achieveÂ  all of understanding indicators, meanwhile for low students achieve one indicator of two indicators. On process aspect, high students achieve all of understanding indicators and average students achieve all of understanding indicators too. Meanwhile low students achieve one indicator of three indicators. On objectaspect,high students achieve all of understanding indicators and average students achieve one indicator of three understanding indicators. Meanwhile for low students do not achieve all of understanding indicators. On schemeaspect, high students achieve all of understanding indicators and for average students achieve two understanding indicators. Meanwhile for low students achieve only oneÂ  indicatorsØØ§ÙÙØª ÙØ°Ù Ø§ÙÙÙØ§ÙØ© Ø¹Ø±Ø¶ ÙÙÙ Ø·ÙØ§Ø¨ ÙØ³Ù ØªØ¹ÙÙÙ Ø§ÙØ±ÙØ§Ø¶ÙØ§Øª ÙÙ Ø§ÙØ¬Ø§ÙØ¹Ø© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© Ø§ÙØÙÙÙÙØ© ØªÙÙÙÙØ¬ Ø£ØºÙÙØ¬Ø Ø¹Ù Ø§ÙØªÙØ§ÙÙØ§Øª Ø¥ÙÙ Ø£Ø¬Ù ØºÙØ± ÙØ³ÙÙÙ Ø¹ÙÙ Ø£Ø³Ø§Ø³ ÙØ¸Ø±ÙØ© Â APOS. ÙÙÙÙØµÙÙ Ø¥ÙÙ Ø§ÙØ£ÙØ¯Ø§ÙØ Ø§ØªÙØ¨Ø¹ ÙØ°Ø§ Ø§ÙØ¨ØØ« Ø§ÙÙÙÙØ¬ Ø§ÙÙÙÙÙØ Ø¨Ø¹Ø±Ø¶ ÙØªØ§Ø¦Ø¬ Ø§Ø³ØªÙØ¹Ø§Ø¨ Ø§ÙÙÙÙ Ø¹ÙÙ Ø£Ø³Ø§Ø³ ÙØ¸Ø±ÙØ© APOS. ÙÙØµØ§Ø¯Ø± Ø§ÙØ¨ÙØ§ÙØ§Øª ÙÙØ°Ø§ Ø§ÙØ¨ØØ« ÙÙ Ø³ØªØªØ© Ø·ÙØ§Ø¨: Ø·Ø§ÙØ¨Ø§Ù Ø°ÙÙÙØ§ÙØ ÙØ·Ø§ÙØ¨Ø§Ù ÙØªÙØ³Ø·Ø§Ù ÙÙ Ø§ÙØ°ÙØ§Ø¡ ÙØ·Ø§ÙØ¨Ø§Ù Ø¶Ø¹ÙÙØ§Ù. Ø¯ÙØª ÙØªØ§Ø¦Ø¬ Ø§ÙØ¨ØØ« Ø¹ÙÙ Ø£Ù ÙÙÙ Ø·ÙØ§Ø¨ ØªØ¯Ø±ÙØ³ Ø§ÙØ±ÙØ§Ø¶ÙØ§Øª ÙÙ Ø§ÙØ¬Ø§ÙØ¹Ø© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© Ø§ÙØÙÙÙÙØ© ØªÙÙÙÙØ¬ Ø£ØºÙÙØ¬ Ø¹ÙÂ  Ø§ÙØªÙØ§ÙÙØ§Øª Ø¥ÙÙ Ø£Ø¬Ù ØºÙØ± ÙØ³ÙÙÙ ÙÙ ÙØ±ØÙØ© Ø§ÙØªØ·Ø¨ÙÙ ÙØ§Ù Ø§ÙØ·Ø§ÙØ¨Ø§Ù Ø§ÙØ°ÙÙØ§Ù ØªÙÙÙØ±Øª ÙÙÙÙØ§ Ø¬ÙÙØ¹ ÙØ¤Ø´Ø±Ø§Øª Ø§ÙÙÙÙØ ÙØªÙÙÙØ± Ø¬ÙÙØ¹ ÙØ¤Ø´ÙØ±Ø§Øª Ø§ÙÙÙÙ ÙØ°ÙÙ ÙÙ Ø§ÙØ·Ø§ÙØ¨ÙÙ Ø§ÙÙØªÙØ³Ø·ÙÙ ÙÙ Ø§ÙØ°ÙØ§Ø¡Ø Ø£ÙØ§ ÙÙ Ø§ÙØ·Ø§ÙØ¨ÙÙ Ø§ÙØ¶Ø¹ÙÙÙÙ ÙØªÙÙÙØ±Øª ÙÙÙÙØ§ ÙØ¤Ø´ÙØ±Ø© ÙØ§ØØ¯Ø© ÙÙØ·. ÙØ£ÙØ§ ÙÙ ÙØ±ØÙØ© Ø§ÙØ¹ÙÙÙØ© ÙØ¥Ù Ø§ÙØ·Ø§ÙØ¨ÙÙ Ø§ÙØ°ÙÙÙÙÙ ØªÙÙÙØ±Øª ÙÙÙÙØ§ Ø¬ÙÙØ¹ ÙØ¤Ø´Ø±Ø§Øª Ø§ÙÙÙÙØ ÙÙÙ Ø§ÙØ·Ø§ÙØ¨ÙÙ Ø§ÙÙØªÙØ³Ø·ÙÙ Ø°ÙØ§Ø¡ ÙØªÙÙÙØ± ÙÙÙÙØ§ Ø¬ÙÙØ¹ ÙØ¤Ø´Ø±Ø§Øª Ø§ÙÙÙÙ ÙØ°ÙÙØ Ø£ÙØ§ ÙÙ Ø§ÙØ·Ø§ÙØ¨ÙÙ Ø§ÙØ¶Ø¹ÙÙÙÙ ÙØªÙÙÙØ±Øª ÙÙÙÙØ§ ÙØ¤Ø´Ø±Ø© ÙØ§ØØ¯Ø© ÙÙØ· ÙÙ Ø«ÙØ§Ø« ÙØ¤Ø´Ø±Ø§Øª. ÙÙÙ ÙØ±ØÙØ© Ø§ÙÙÙØ¶ÙØ¹Ø ÙØ¥Ù Ø§ÙØ·Ø§ÙØ¨ÙÙ Ø§ÙØ°ÙÙÙÙ ØªÙÙÙØ± ÙÙÙÙØ§ Ø¬ÙÙØ¹ ÙØ¤Ø´Ø±Ø§Øª Ø§ÙÙÙÙØ ÙØ§ÙØ·Ø§ÙØ¨Ø§Ù Ø§ÙÙØªÙØ³Ø·Ø§Ù ÙØªÙÙÙØ± ÙÙÙÙØ§ ÙØ¤Ø´Ø±Ø© ÙØ§ØØ¯Ø© ÙÙØ· ÙÙ Ø«ÙØ§Ø« ÙØ¤Ø´Ø±Ø§Øª Ø§ÙÙÙÙØ ÙØ£ÙØ§ Ø§ÙØ·Ø§ÙØ¨Ø§Ù Ø§ÙØ¶Ø¹ÙÙØ§Ù ÙÙØ§ ØªØªÙÙÙØ± ÙÙÙÙØ§ Ø£ÙØ© ÙØ¤Ø´Ø±Ø© ÙÙ Ø«ÙØ§Ø« ÙØ¤Ø´Ø±Ø§Øª Ø§ÙÙÙÙ. ÙØ£ÙØ§ ÙÙ ÙØ±ØÙØ© Ø§ÙØªØ®Ø·ÙØ· ÙØ¥Ù Ø§ÙØ·Ø§ÙØ¨ÙÙ Ø§ÙØ°ÙÙÙÙ ØªÙÙÙØ±Øª ÙÙÙÙØ§ Ø¬ÙÙØ¹ ÙØ¤Ø´Ø±Ø§Øª Ø§ÙÙÙÙØ ÙÙÙ Ø§ÙØ·Ø§ÙØ¨ÙÙ Ø§ÙÙØªÙØ³Ø·ÙÙ ØªÙÙØ±Øª ÙÙÙÙØ§ ÙØ¤Ø´Ø±ØªØ§Ù ÙÙØ·Ø ÙØ£ÙØ§ ÙÙ Ø§ÙØ·Ø§ÙØ¨ÙÙ Ø§ÙØ¶Ø¹ÙÙÙÙ ÙØªÙÙÙØ±Øª ÙÙÙÙØ§ ÙØ¤Ø´Ø±Ø© ÙØ§ØØ¯Ø© ÙÙØ·